Beetroot and radish powders as natural nitrite source for fermented dry sausages. (January 2021) - Ozaki, Maristela Midori; Munekata, Paulo E.S.; Jacinto-Valderrama, Rickyn Alexander; Efraim, Priscilla; Pateiro, Mirian; Lorenzo, José Manuel; Pollonio, Marise Aparecida Rodrigues
Abstract: The aim of this study was to investigate the use of radish and beetroot powders as potential substitutes of nitrite in fermented dry sausages due to their high nitrate content (around 16, 000 and 14, 000 mg/kg, respectively). Six treatments were prepared and evaluated during the ripening process and storage time: C1 (control with 150 mg/kg sodium nitrite and 150 mg/kg sodium nitrate), C2 (control without sodium nitrite/nitrate), R05 (0.5% radish powder), R1 (1% radish powder), B05 (0.5% beetroot powder) and B1 (1% beetroot powder). The addition of vegetable powders influenced moisture content, weight loss and water activity of sausages. Nitrite was formed from radish and beetroot powders during the ripening process, especially in R1 and B1 treatments. Beetroot powder affected colour, pigments and lactic acid bacteria counts. The results of pH, colour, lipid oxidation, nitrite and nitrate analysis suggest R1 treatment as a potential nitrite replacer obtained from a simple and feasible drying process. Highlights: Vegetable powders as natural alternatives to nitrites in meat products. Radish and beetroot powders have antioxidant activity and high nitrate content. Beetroot betalain affected the colour of fermented dry sausages. Radish and beetroot powders significantly decreased water activity (aw ) of products during processing. Colour change and lipid oxidation in sausages were inhibited by radish powder.